Desain Proses Produksi dalam Proyek Pembuatan Mesin Pencacah Kompos pada Kegiatan di PT Raja Ampat Indotim - Surya, Raygalan Kalmas; Maksum, Apid Hapid (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The performance of the industrial system in producing goods will be very important for business continuity, such as meeting consumer demand so that it can maintain the sustainability and/or continuity of the company in order to survive. Currently, companies will always be required to maintain and improve their competitive capabilities, so one way to do this is by increasing productivity at all levels within the company. The author tries to identify the work process of PT. Raja Ampat Indotim in the production of Compost Chopper Machines due to the results of interviews conducted at the company, there were no procedures for the work process in producing Compost Chopper Machines, so on this occasion the author intends to design a standard work process in the production of compost chopper machines at PT. Raja Ampat Indotim. Data processing in this research was carried out using an Operation Process Map. Based on the operational process map that has been created, the time required to produce a Compost Shredding Machine is 968.29 minutes.